"Nurses are every bit of the flow:" Emergency department nurses' conceptualization of patient flow management. Issue 6 (18th November 2022) - Benjamin, Ellen; Wolf, Lisa A.
Abstract: Aim: To validate and refine Benjamin and Jacelon's 2021 definition of patient flow management using the experience and knowledge of practicing emergency department nurses. Background: Patient flow requires complex, real‐time decision‐making to match patients to limited resources and facilitate their movement through care processes. A literature‐based concept analysis of patient flow management was first performed in 2021, but the voice of nurses is largely absent from existing patient flow research. Design: This study employed an expanded concept analysis methodology, as articulated by Kathleen Cowles. Data source: Focus groups of nine emergency nurses were conducted. Results: Emergency nurses' conceptualization of patient flow management differs from the definition as it has emerged through patient flow literature. Patient flow management is a nurse‐driven process that relies on nursing knowledge and the work of all emergency nurses, including bedside nurses. Emergency nurses perceive the ultimate goal of patient flow management to be the collective safety of patients, and they work to promote patient safety within their own scope of responsibility. Conclusion: Understanding patient flow management as a nurse‐driven process emphasizes the importance of nurse training and capacity to effective patient flow. Future research should explore the role of emergency nurses as active directors, rather than passive components, of patient flow. More work is needed to investigate this complex nursing task.